KEWENANGAN BANK INDONESIA DALAM PENGATURAN DAN PENGAWASAN PERBANKAN SETELAH TERBITNYA UNDANG-UNDANG NO 21 TAHUN 2011 TENTANG OTORITAS JASA KEUANGAN (JURNAL HUKUM SEHASEN, 2015)
Bank Indonesia is the central bank of Indonesia which has the authority as the monetary authority (monetary authority) and to supervise and regulate banking institutional. To keep the independency of Bank Indonesia, based on Bank Indonesia Law 23/99 Article 34 paragraph (1) and (2) then formed the Financial Services Authority (OJK) on 22 November 2011, the OJK has the function of regulation and supervision of banking in Indonesia. Banking regulation by the OJK considered not have the legal basis for the establishment OJK formed to the banking supervision is considered that Bank Indonesia has failed to carry out these functions while the banking arrangements are retained by Bank Indonesia in accordance with the explanation of Article 34 paragraph (2) of the Act of Bank Indonesia, not only that delay the establishment of the OJK also considered unconstitutional by some parties that the filing of a lawsuit to download the OJK Act judicial review to the Constitutional Court (MK). Establishment of the OJK that no delay occurs then make FSA unconstitutional but the OJK when examined under Law 12/11 on the establishment of legislation, the OJK is a constitutional institution but when examined the substance of the Act OJK then indeed there is debate as function settings question will cause the function to implement and establish a system of payment by Bank Indonesia smoothness will automatically fall under the authority of the OJK for implementing and applying the regulatory function of the payment system is one of the activities in the regulation and supervision of banks that will lead to the health of financial institutions, especially banks can be controlled and detected earlier if there are indications of deterioration of the financial condition of banking which will lead to a suspension / closure of banking activities Keywords: Bank Indonesia, Law No 21 Year 2011 Regarding The Financial Services Authority, Regulatory Authority And Banking Supervision